Megakaryocytic emperipolesis and platelet function abnormalities in five patients with gray platelet syndrome. (17th November 2015) - Larocca, Luigi M.; Heller, Paula G.; Podda, Gianmarco; Pujol-Moix, Nuria; Glembotsky, Ana C.; Pecci, Alessandro; Alberelli, Maria Adele; Balduini, Carlo L.; Landolfi, Raffaele; Cattaneo, Marco; De Candia, Erica
Abstract: The gray platelet syndrome (GPS) is a rare congenital platelet disorder characterized by mild to moderate bleeding diathesis, macrothrombocytopenia and lack of azurophilic α-granules in platelets. Some platelet and megakaryocyte (MK) abnormalities have been described, but confirmative studies of the defects in larger patient cohorts have not been undertaken. We studied platelet function and bone marrow (BM) features in five GPS patients with NBEAL2 autosomal recessive mutations from four unrelated families. In 3/3 patients, we observed a defect in platelet responses to protease-activated receptor (PAR)1-activating peptide as the most consistent finding, either isolated or combined to defective responses to other agonists. A reduction of PAR1 receptors with normal expression of major glycoproteins on the platelet surface was also found. Thrombin-induced fibrinogen binding to platelets was severely impaired in 2/2 patients. In 4/4 patients, the BM biopsy showed fibrosis (grade 2–3) and extensive emperipolesis, with many (36–65%) MKs containing 2–4 leukocytes engulfed within the cytoplasm. Reduced immunolabeling for platelet factor 4 together with normal immunolabeling for CD63 in MKs of two patients demonstrated that GPS MKs display an alpha granule-specific defect. Increased immunolabeling for P-selectin and decreased immunolabeling for PAR1, PAR4 and c-MPL were also observed in MKs of two patients. Marked emperipolesis, specific defect of MK alpha-granule content and defect of PAR1-mediated platelet responses are present in all GPS patients that we could study in detail. These results help to further characterize the disease.